5=-8.7+6x

Simple and best practice solution for 5=-8.7+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=-8.7+6x equation:


Simplifying
5 = -8.7 + 6x

Solving
5 = -8.7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + -6x = -8.7 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -6x = -8.7 + 0
5 + -6x = -8.7

Add '-5' to each side of the equation.
5 + -5 + -6x = -8.7 + -5

Combine like terms: 5 + -5 = 0
0 + -6x = -8.7 + -5
-6x = -8.7 + -5

Combine like terms: -8.7 + -5 = -13.7
-6x = -13.7

Divide each side by '-6'.
x = 2.283333333

Simplifying
x = 2.283333333

See similar equations:

| f(x)=5cos(x) | | 3/4=15/x2 | | -4x^2-52x+120=0 | | 3(x-5)2(x-1)=8 | | 4(5x+4)=236 | | 8t+48t+t^2= | | 2x^3-32x^2+78x=0 | | 2w-4=4 | | 7-3*2+6+3=35 | | 1.86=6.2a | | 25x^3-15x^4=5x^3 | | -30+5(x-2)=4x+7 | | 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 |

Equations solver categories